Curing neurophobia in medical schools: evidence-based strategies. Issue 1 (1st January 2016) - Abushouk, Abdelrahman Ibrahim; Duc, Nguyen Minh
Abstract : Medical students often perceive neurology as the most difficult medical specialty. This perception is described as 'neurophobia' in the medical literature. Several studies have cited poor teaching, complex examination, and separation of basic and clinical sciences as major factors in the development of neurophobia. These negative perceptions can have serious implications, such as decreasing the students' desire to consider neurology as a future career and increasing referrals from other specialists to avoid dealing with neurological conditions. Faced with increasing demands of healthcare systems and the global burden of neurological conditions, there is a rising need for further research and innovative strategies to improve students' perceptions of clinical neurology. This review discusses evidence-based recommendations and educational interventions to cure neurophobia in medical education.